Proposing A Nonmainstream Concept of Corporate Social Responsibility through Islamic Perspective - Rahmanti, Virginia Nur; Agustia, Dian; Setiawan, Achdiar Redy (Jurusan Akuntansi Politeknik Negeri Malang, 2024)
Abstract: Proposing A Nonmainstream Concept of Corporate Social Responsibility through Islamic Perspective Purpose: This article aims to criticize the concept of CSR from an Islamic perspective. Method: Researchers employed hyper-post phenomenology as a methodological approach. Results: The results show that the practice of CSR by Islamic banks in Indonesia has shifted from social to material goals. CSR is only a legitimization tool for